2021
DOI: 10.3390/min11101037
|View full text |Cite
|
Sign up to set email alerts
|

Regional Geochemical Anomaly Identification Based on Multiple-Point Geostatistical Simulation and Local Singularity Analysis—A Case Study in Mila Mountain Region, Southern Tibet

Abstract: The smoothing effect of data interpolation could cause useful information loss in geochemical mapping, and the uncertainty assessment of geochemical anomaly could help to extract reasonable anomalies. In this paper, multiple-point geostatistical simulation and local singularity analysis (LSA) are proposed to identify regional geochemical anomalies and potential mineral resources areas. Taking Cu geochemical data in the Mila Mountain Region, southern Tibet, as an example, several conclusions were obtained: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Numerous studies have used fractal and correlation analysis and machine learning methods to identify potential mineralization zones separately [5,9,[18][19][20][21][22][23][24][25]. However, a few studies have used integrated and hybrid methods for the geochemical modeling of ore mineralization [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have used fractal and correlation analysis and machine learning methods to identify potential mineralization zones separately [5,9,[18][19][20][21][22][23][24][25]. However, a few studies have used integrated and hybrid methods for the geochemical modeling of ore mineralization [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…However, a great many of the previous studies focused on the screening and verification of geochemical anomalies with high concentration, multiple elements, and large size [18][19][20]. With the deepening of mineral prospecting, it can be generally found that the geochemical anomalies in mineralized bodies with large buried depth are very weak with low concentration and small-sized; hence, they are always ignored [21][22][23][24][25]. Therefore, it is of great significance to (a) summarize previous research and regional geochemical data of China, (b) identify the missed geochemical anomalies mentioned above, (c) establish geochemical models of metallogenic indicator elements for typical deposits, (d) explore the geochemical distribution of elements and its relationship with regional metallogeny and metallogenic potential, and (e) evaluate the potential for mineral resources.…”
Section: Introductionmentioning
confidence: 99%
“…The mineral resource deposits are modelled and categorized by N. Battalgazy and N. Madani [9], who employed the projection pursuit multivariate transformation method, and then, the outputs are compared with conventional (co)-simulation methods. Li et al [10] proposed multiple-point geostatistical simulation and local singularity analysis to identify regional geochemical anomalies and potential mineral resource areas. Liu et al [11] constructed 3D geometric models for evaluating the Dawangding gold deposit in south China using the FLAC3D (fast Lagrangian analysis of continua in three dimensions) modelling.…”
Section: Introductionmentioning
confidence: 99%